2021
DOI: 10.1371/journal.pone.0258156
|View full text |Cite
|
Sign up to set email alerts
|

Loss of telomere silencing is accompanied by dysfunction of Polo kinase and centrosomes during Drosophila oogenesis and early development

Abstract: Telomeres are nucleoprotein complexes that protect the ends of eukaryotic linear chromosomes from degradation and fusions. Telomere dysfunction leads to cell growth arrest, oncogenesis, and premature aging. Telomeric RNAs have been found in all studied species; however, their functions and biogenesis are not clearly understood. We studied the mechanisms of development disorders observed upon overexpression of telomeric repeats in Drosophila. In somatic cells, overexpression of telomeric retrotransposon HeT-A i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…1I), suggesting defective ovulation. De-repression of HeT-A in germ cells causes abnormal mitosis in early embryos and leads to lethality with maternal effect (Morgunova et al ., 2015; Morgunova et al ., 2021). However, these mutants lay eggs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1I), suggesting defective ovulation. De-repression of HeT-A in germ cells causes abnormal mitosis in early embryos and leads to lethality with maternal effect (Morgunova et al ., 2015; Morgunova et al ., 2021). However, these mutants lay eggs.…”
Section: Resultsmentioning
confidence: 99%
“…These unique features of telomere maintenance by retrotransposons in D. melanogaster look like a symbiosis between host and retrotransposon (Pardue and Debaryshe, 2002). However, de-repression of HeT-A retrotransposon in germ cells causes severe embryo abnormalities (Morgunova et al, 2015; Morgunova et al, 2021), and recent genomic analysis of the other Drosophila species has suggested that these retrotransposons have evolved very rapidly and replicated their copy number selfishly rather than symbiotically (Saint-Leandre et al, 2020; Saint-Leandre et al, 2019). Therefore, the host must regulate the activity of telomeric retrotransposons.…”
Section: Introductionmentioning
confidence: 99%
“…TEIF was found to positively correlate with CA in colorectal tumors [75]. Telomere dysfunction induced in Drosophila oogenesis caused deregulation of centrosome biogenesis, leading to embryonic lethality [22]. Since CA also elicits CIN and genomic instability, telomere dysfunction may cause CIN and aneuploidy to arise in pre-neoplastic HMECs or early stage lesions.…”
Section: Bypassing the Replicative Cellular Senescence Barrier: Kifc1 And Loss Of Telomere Function And Genomic Stabilitymentioning
confidence: 99%
“…Specifically, CA has been found to increase from atypical ductal hyperplasia (ADH) to ductal carcinoma in situ (DCIS), to increase with higher DCIS grade, and to be more prevalent in TNBC versus non-TNBC tumors [20,21]. CA has also been shown to be associated with chromosomal instability (CIN) and aneuploidy in early stage breast lesions as well as being linked to cell cycle deregulation, telomere dysfunction, and cellular senescence [15,16,[22][23][24][25]. Furthermore, induction of CA in non-transformed cell lines has been shown to be sufficient to induce tumorigenesis and to mimic oncogene-induced cellular invasion [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…These unique features of telomere maintenance by retrotransposons in D. melanogaster resemble a symbiosis between the host and retrotransposon ( 20 ). However, de-repression of HeT-A retrotransposon in germ cells causes severe embryo abnormalities ( 33 , 34 ), and a recent genomic analysis of other Drosophila species has suggested that these retrotransposons evolve rapidly and replicate their copy number selfishly rather than symbiotically ( 21 , 26 , 35 ). Therefore, the host must regulate the telomeric retrotransposon activity.…”
Section: Introductionmentioning
confidence: 99%